The clinico-etiological profile of febrile seizure and its association with serum ferritin level - Dr. Shailendra Gautam; Dr. Pir Pratap Singh; Dr. Santosh Kumar Barman; Dr. Arun Kumar Arya (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Febrile seizures are defined as an event in infancy or childhood, usually occurring between6 months and 5 years of age, associated with fever but without evidence of intracranial infection or other definable cause Thus, the present study was conducted to determine any association between serum ferritin level and first febrile seizure.Methods: A cross sectional study was conducted among the infants of age group 6 month to 5 year with complaints of fever with seizures attending Department of Pediatrics, GSVM Medical College, Kanpur for Feb. 2017 to Oct. 2018. After approval from Institutional Ethics Committee. Data was collected on pre deign case sheet consisting of general information history, clinical examination, temperature recording and relevant laboratory investigation such as hemoglobin, total leucocyte count, differential leucocyte count and serum ferritin levels. Statistical analysis was done using SPSS (version 24.0; SPSS Inc., Chicago, IL, USA).Results: Study found that among 50 children, 40% children of febrile seizure belonged to age group 1 year to 2 years; febrile seizure was predominantly present in male population. Type of febrile seizure was predominantly simple febrile seizure (72%) and complex febrile seizure (28%). Results of GTCS it clearly indicate that there is statically significant association of GTCS with low serum ferritin level of less than 10 ng.Conclusions: In ferritin less than 10 ng, 29(90.6%) patients had GTCS and which was statistically significant. Association of cause of fever vs. serum ferritin was statistically significant. Larger studies are needed to confirm the present findings.